The impact of flap design on swelling, trismus, and pain after the lower third molar surgery: buccal triangular flap vs. envelope flap - Matijević, Stevo; Djordjević, Filip; Vukašinović, Mila; Bukumirić, Zoran; Dubovina, Dejan (Vojnosanitetski pregled, 2024)
Background/Aim. Swelling, trismus, and pain (STP) are the most common complications that occur after the surgical extraction of impacted lower third molars (LTM). Buccal triangular and envelope flaps are the two most commonly used mucoperiosteal flaps in LTM surgery. The aim of this study was to compare the possible impact of these two types of flaps on the occurrence and intensity of postoperative STP after the surgical extraction of impacted LTMs. Methods. The study included 30 adult patients of both genders, with fully impacted LTMs in vertical position according to Winter classification and class I or II, and position A or B, according to Pell and Gregory classification. All patients were randomly divided into two groups depending on the type of the applied mucoperiosteal flap (triangular or envelope type). The degree of edema, interincisal distance (trismus), and the level of pain were evaluated preoperatively and at each follow-up (on the first, second, and seventh day postoperatively). Results. No statistically significant difference was found among the examined groups in terms of STP reduction in the postoperative period (p > 0.05). Conclusion. The choice of mucoperiosteal flap design, buccal triangular or envelope, during the surgical extraction of impacted LTMs has no impact on the intensity of postoperative STP.
Keywords: edema; molar, third; oral surgical procedures; pain; postoperative complications; surgical flaps; tooth, impacted; trismus